#### Answer

x = 11

#### Work Step by Step

Solve: 3x - 6 = 2x + 5
3x - 6 = 2x + 5
3x - 6 - 2x = 2x + - 2x
x - 6 = 5
x - 6 + 6 = 5 + 6
x = 11

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

x = 11

Solve: 3x - 6 = 2x + 5
3x - 6 = 2x + 5
3x - 6 - 2x = 2x + - 2x
x - 6 = 5
x - 6 + 6 = 5 + 6
x = 11

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.